A topical BRAF inhibitor (LUT-014) for treatment of radiodermatitis among women with breast cancerCapsule Summary - Sanford Katz, MD; Doug Ciuba, MD; Antoni Ribas, MD, PhD; Noa Shelach, PhD; Galit Zelinger, BS; Briana Barrow, BS; Benjamin W. Corn, MD (Elsevier, 2024)
Background: Modern radiotherapy is associated with dermatitis (RD) in approximately one-third of patients treated for breast cancer. There is currently no standard for treating RD. Objective: The objective of this study was to determine whether LUT014, a topical BRAF inhibitor which paradoxically activates mitogen-activated protein kinase, can safely improve RD. Methods: A phase I/II study was designed to first follow a small cohort of women with grade 2 RD regarding toxicity and response. Then, 20 patients were randomized to compare LUT014 to "vehicle" relative to safety and response (measured with common terminology criteria for adverse events, Dermatology Life Quality Index). Results: No substantial toxicity (eg, 0 serious adverse event) was associated with LUT014. All 8 women receiving LUT014 achieved treatment success (5-point Dermatology Life Quality Index reduction at day 14) compared to 73% (8/11) on the placebo arm (P = .591). The time to complete recovery was shorter in the treatment arm. Limitations: The sample size was limited. Only 2 hospitals were included. Conclusions: Topical LU014 is tolerable and may be efficacious for grade 2 RD.